Intellectual capital and its increasing relevance. - Chee, Khoon Kiat. (2008)
This project examines the effect of three factors -- information intensity of industry, number of employees and Internet capabilities -- on the value of Intellectual Capital. Three hypotheses were formulated and tested using financial data collected from a sample of 136 organisations. The results show that Intellectual Capital value is higher in high information intensity companies and that organisations should be aware of the importance of human capital to the intangible value of the firm.